Kewenangan KPK Dalam Memeriksa Tindak Pidana Korupsi Pada Bank Indonesia - Zakaria Tribrata Widya Saputra; Muhammad Syahrul Borman; Moh. Taufik (JURNAL RECHTENS, 2025)
The study analyzes the legal framework governing KPK’s authority, including Law Number 19 of 2019 on the KPK, the Anti-Corruption Law, and financial governance regulations related to the distribution of social assistance. Using a normative juridical method supported by statutory and conceptual approaches, this paper identifies the extent to which KPK can intervene in corruption cases involving state financial management within independent state institutions such as Bank Indonesia. Findings show that the KPK holds strong legal authority to investigate corruption offenses, especially when they involve potential state losses and violations of governance principles. The study also reveals several challenges, including coordination barriers among supervisory institutions and the complexity of Bank Indonesia’s internal mechanisms. This article contributes to the discourse on strengthening anti-corruption mechanisms in Indonesia and highlights the urgency of improving transparency and accountability in the management of national social assistance funds.